Wajh al-Munâsabah fî Surah al-Isrâ’ al-Ayat 18-22 ‘inda Ibn ‘Âsyûr fî Tafsîrihi at-Tahrir Wa at-Tanwir - Ali Mahfuz Munawar; Risna. Baco (Universitas Darussalam Gontor, 2019)
Al-munasabah is a science which has an important role within al-Qur'an tafseer studies, because this study examines the contents of al-Qur'an by finding the correlation of it’s verses. On the other hand some orientalist spread the stigma to against al-Qur'an in over time by dedicating that al-Qur'an and it’s verses are not systematic. Based on this statement, writer choose Ibnu Asyur because he is the only one who applied exegetes science of al-munasabah in al-Qur'an. He also proved that unsystematic of al-Qur'an is being one of I'jaz al-Qur'an. Then, this is a main reason to deny orientalist minded. It have a correlation and compliance between verses with another’s, from the first verse discussed the earthly desires, correlated with the later paragraph that have a desire of hereafter. Both of verses are inter-related to bring up the secrets of the two differenc of verbs within it. The next verse investigates about the glory of Allah that spread along his creature without any differentiation. Allah SWT gives a description about Prophet Muhammad SAW as a purely human who get his mercy as a role model of good character for human being to carry out a favor and leave the vise versa to get his glory in the afterlife, it was because that Allah warned his creature to renounce the Act of shirk, because this act that caused the absence of God in afterlif.